Search for the Dimuon Decay of the Higgs Boson in pp Collisions at √s =13 TeV with the ATLAS Detector - Alconada Verzini, María Josefina (2017)
A search for the dimuon decay of the Higgs boson was performed using data corresponding to an integrated luminosity of 36.1 fb-1 collected with the ATLAS detector in pp collisions at √s=13 TeV at the Large Hadron Collider. No significant excess is observed above the expected background. The observed (expected) upper limit on the cross section times branching ratio is 3.0 (3.1) times the Standard Model prediction at the 95% confidence level for a Higgs boson mass of 125 GeV. When combined with the pp collision data at √s=7 TeV and √s=8 TeV, the observed (expected) upper limit is 2.8 (2.9) times the Standard Model prediction.